2009
DOI: 10.1039/b814246g
|View full text |Cite
|
Sign up to set email alerts
|

A potential ionic liquid for CO2-separating gas membranes: selection and gas solubility studies

Abstract: The production of hydrogen from fossil fuels by steam reforming/water gas shift can be enhanced by separating the reaction byproduct, CO 2 , within the reactor as it is produced. Such a separationenhanced reaction not only has higher conversion efficiency, but can also be considered a greener process which produces high-purity hydrogen with little CO 2 contamination. Supported ionic liquid membranes may be able to achieve this separation task since they are known to have high CO 2 and low H 2 solubilities. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 41 publications
5
95
1
Order By: Relevance
“…The solubilities of carbon dioxide (CO 2 ), methane (CH 4 ), ethane (C 2 H 6 ) and propane (C 3 H 8 ) in several ILs have been studied intensively [1][2][3][4][5]. From these solubility studies, it can be concluded that ILs are promising absorbents for the removal of CO 2 from natural gas streams [6][7][8]. Especially interesting for CO 2 capture is the IL 1-ethyl-3-methylimidazolium tris(pentafluoroethyl) trifluorophosphate ([emim][FAP]), because of its high bulk solubility for CO 2 compared to the much lower bulk solubilities of CH 4 , C 2 H 6 and C 3 H 8 as measured previously using a synthetic method with the Cailletet apparatus [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…The solubilities of carbon dioxide (CO 2 ), methane (CH 4 ), ethane (C 2 H 6 ) and propane (C 3 H 8 ) in several ILs have been studied intensively [1][2][3][4][5]. From these solubility studies, it can be concluded that ILs are promising absorbents for the removal of CO 2 from natural gas streams [6][7][8]. Especially interesting for CO 2 capture is the IL 1-ethyl-3-methylimidazolium tris(pentafluoroethyl) trifluorophosphate ([emim][FAP]), because of its high bulk solubility for CO 2 compared to the much lower bulk solubilities of CH 4 , C 2 H 6 and C 3 H 8 as measured previously using a synthetic method with the Cailletet apparatus [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study proved that supported liquid membranes (SLMs) that were immobilized with RTILs were stable for gas-gas separations [84]. Some recent affords have been taken by different researchers worldwide to study the gas separation [85][86][87][88][89][90][91][92][93][94].…”
Section: Extraction Process By Supported Ionic Liquid Membranesmentioning
confidence: 99%
“…Thus, ILs are frequently regarded as a class of ''green" solvents lack of volatility to reduce a risk of air pollution. Recently, several researchers [3][4][5] have reported that solubilities of acidic gases such as CO 2 , SO x , and NO x are remarkably high, while normal gases, N 2 , O 2 , and H 2 are quite sparingly soluble in some typical imidazolium-based ILs. These unique properties of ILs could promisingly provide opportunity to create a new ''green" CCS technology, in particular, based on physical absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop such CCS process using ILs, comprehensive understandings of IL-gas systems are necessary from the thermodynamic as well as kinetic viewpoints. Although solubilities of gases in ILs have been investigated experimentally [3][4][5][6][7] and theoretically [8][9][10], there have been a few studies [11][12][13][14][15][16][17] on transport phenomena in ILs mixed with gases in spite of their importance to predict absorption and desorption rates of gases in relatively viscous ILs. Several researchers [11][12][13] presented the diffusion coefficients of CO 2 in ILs by means of transient absorption technique; however, they were available only at relatively low pressures.…”
Section: Introductionmentioning
confidence: 99%